Surgical treatment of iatrogenic rectourinary fistula-York-Mason technique-a case report - Santos, P (2011)
Introduction. Recto-urinary fistulas resulting from trauma or surgery are a serious and debilitating complication. They represent a challenge not only because of the difficulty on choosing the best technique to solve them but also because of the risk of recurrence. Spontaneous cure is rare. Materials and Methods. We describe the case of a 61-years-old man that on the 9th postoperative day of a laparoscopic radical prostatectomy (LRP) started with fecaluria and liquid faeces. Recto-urinary fistula was confirmed at the 10th postoperative day by CT scan and contrast enema. Discussion. We chose the York-Mason technique, because it is simple to perform, effective and hasminimalmorbidity. This is a posterior, transrectal, and transsphincteric approach, carried out on healthy tissues without previous scarring phenomena. Results. The postoperative period progressed without complications, and the patient discharged on the 4th day. The closure of the fistula was confirmed radiologically by retrograde cystography after 4 weeks allowing the removal of drainage catheter. The reconstruction of intestinal transit was carried out 2 months later. Conclusion. The York-Mason technique, a transrectal and transsphincteric approach with minimalmorbidity, proved to be effective on the resolution of the recto-urinary fistula, a rare complication of the radical prostatectomy